Penjor in Hindu Communities: A symbolic phrases of relations between human to human, to environment, and to God - I Gst. Pt. Bagus Suka Arjawa; I Gst. Agung Mas Rwa Jayantiari (Masyarakat, Kebudayaan dan Politik, 2020)
The purpose of this article was to observe the development of the social meaning derived from penjor (bamboo decorated with flowers as an expression of thanks to God) for the Balinese Hindus. In the beginning, the meaning of penjor serves as a symbol of Mount Agung, and it developed as a human wisdom symbol. This research was conducted in Badung and Tabanan Regency, Bali using a qualitative method. The time scope of this research was not only on the Galungan and Kuningan holy days, where the penjor most commonly used in society. It also used on the other holy days, including when people hold the caru (offerings to the holy sacrifice) ceremony, in the temple, or any other ceremonial place and it is also displayed at competition events. The methods used were hermeneutics and verstehen. These methods served as a tool for the researcher to use to interpret both the phenomena and sentences involved. The results of this research show that the penjor has various meanings. It does not only serve as a symbol of Mount Agung and human wisdom; and it also symbolizes gratefulness because of God’s generosity and human happiness and cheerfulness. Penjor is a Tri Hita Karana (harmonious relationship between humans, humans with the environment, and humans with God) symbol.